Pengaruh Modal dan Penggunaan Online Food Delivery terhadap Pendapatan di CV. Fada Food - Riski Fardatus Samadiyah, Nur; Baidlowi, Imam; Verlandes, Yuliasnita (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to evaluate how capital and utilization of online food delivery services affect CV Fada Food's revenue. This study applies a quantitative method using multiple linear regression analysis with the help of SPSS version 27 for Windows. The data analyzed came from CV Fada Food's financial transactions in the period 2021 to 2023. The results of the study show that capital has a positive and significant effect on CV Fada Food's revenue. The greater the amount of capital invested, the higher the income generated by the company. In addition, the use of online food delivery services also has a significant positive impact on revenue. By utilizing the food delivery application platform, CV Fada Food can increase customer reach and effectively increase their income.